Analgesic effects of microwave ablation of bone and soft tissue tumors under local anesthesia - Kastler, Adrian; Alnassan, Hussein; Pereira, Philippe L.; Alemann, Guillaume; Barbé, Daniel-Ange; Aubry, Sébastien; Tiberghien, Florence; Kastler, Bruno (Pain medicine, 2013)
To assess the feasibility and efficacy of microwave ablation (MWA) of painful refractory bone and soft tissue tumors performed under local anesthesia.A retrospective study between 2011 and 2013.A single center, Academic Interventional Pain Management Unit.Fifteen patients with 25 refractory painful bone (N = 19) or soft tissue (N = 6) tumors treated with MWA were consecutively included.Local Institutional Review Board approval was obtained, and written informed consent was waived. Lesions included spinal (N = 3), sacral (N = 4), and extraspinal (N = 18) locations. Pain was measured on a visual analog scale (VAS) from 0 to 10 before and immediately after procedure, at 1 week, and on a monthly basis following procedure. MWA procedures were always performed under computed tomography guidance and local anesthesia along with nitrous oxide inhalation.Mean ablation time was 4.09 minutes (range 1-11) with an average of 4.2 cycles with a mean ablation power of 60 W. Preprocedure mean VAS score was 7.2 ± 0.97 (range 6-9). Follow-up postprocedure VAS scores were as follows: day 0: 1.64 ± 1.86, day 7: 1.82 ± 1.79, month 1: 2.05 ± 2.03 (14/15 patients), month 3: 2.13 ± 1.81, month 6: 2.36 ± 2.17; and were statistically significant (P < 0.001). Mean pain relief was 5.5 months.MWA is feasible, safe, and effective in the management of painful refractory bone and soft tissue tumors. It may therefore be considered as a potential alternative to existing percutaneous ablation techniques in the management of bone and soft tissue tumors.